MAPPING PRACTICES AND REFLECTIONS ON SEXUAL RIGHTS:: INTEGRATIVE REVIEW (Interdisciplinary Studies Journal, 2024)
This is a qualitative, descriptive-exploratory study. Its objective is to conduct an integrative literature review to examine the commonalities and differences between the foundations and reflections of studies that address Sexual and Reproductive Rights in dialogue with the field of Education. At the conclusion of the survey, 11 articles were selected and discussed in three distinct, mutually exclusive categories: Central category: foundations for universal citizenship, subdivided into three subcategories: 1.1 LGBT identity rights (3 articles); 1.2 women's rights (6 articles); and 1.3 theoretical foundations against discrimination of sexuality and gender (2 articles). A limitation identified in the study relates to the available literature on the topic, as it temporally diverges from the emancipatory discussions that the state-of-the-art review enabled in the introduction, which problematizes the issue. Despite this, decolonial, decolonizing, and postcolonial studies are becoming increasingly prevalent. On this basis, we argue for the need for works that are independent of the universalist model and that critically examine their epistemological roots in relation to both action and the understanding of reality.
Keywords: Pratices; Reflections; Sexual Rights; Sexuality